Mechanical and tribological behavior of red clay ceramic tiles coated with fly ash powders by thermal sparying technique (2017)
The mechanical and tribological performance of red clay ceramic tiles uncoated and coated by oxy-fuel thermal spraying process from fly ash powders was evaluated. The ceramic tile substrates were manufactured by uniaxial pressing at 26.17 bar pressure, and sintered at 1100 °C. The coating thickness was determined based on the number of projection-cycles oxyacetylene flame over substrate. Coal fly ash coatings were deposited, with average thickness of 56.18±12.18 µm, 180.42±20.32 µm, and 258.26±25.88µm. The mechanical resistance to bending and wear by abrasion deep, were studied using ISO 10545-4 standards and ISO 10545-6 respectively; adhesion was measured using Elcometer equipment Type III according to ASTM D-4541-02 and the average roughness (Ra) was found according to ASTM standard D7127-13, using the profilometer Mitutoyo SJ 201. The surface morphology presented the heterogeneous molten or semi molten splats with average size of 35.262±3.48 micrometers with good adhesion, justifying increased mechanical resistance to bending by 5%, as well as wear by abrasion deep. These results contribute to the development of ceramic products with added value, to be used in various technological applications.